Competitiveness of Russian Universities in the Global System of Higher Education: Quantitative Analysis - D. A. Endovitsky; V. V. Korotkikh; M. V. Voronova (Moscow Polytechnic University, 2020)
Purpose - quantitative analysis and identification of determinants of Russian universities' global competitiveness.Methods. Parametric and non-parametric methods for data analysis and machine learning.Results. The authors figured out the hidden determinants of international competitiveness of Russian universities and the national educational system of the Russian Federation. We proposed four working hypotheses. (1) The positions of Russian universities in the international QS ranking are different for metropolitan and regional universities. (2) The positions of Russian universities in the international QS ranking depend on the status of universities. (3) The positions of Russian universities in the international QS ranking differ depending on the participation of universities in the Russian Academic Excellence Project "5-100". (4) The positions of Russian universities in the international QS ranking are different depending on the level of annual university income. We obtained dataset for the study from the analytical materials of the British consulting company QS, as well as information and analytical materials from the results of monitoring the effectiveness of educational institutions of higher education in the Russian Federation.Conclusions. In the empirical part, we have established the significance of the university geographical location influence on its international competitiveness. We have found a high competitiveness level of Moscow and St. Petersburg universities. The international market for educational services does not give preference to universities with the status of a «national research» or «federal». Increased state funding, burdened with approved roadmaps of the Project Office of the Program 5-100, contributes to competitiveness only in the regional educational markets, which is still not enough to strengthen the global international competitiveness of Russian universities and the national educational system of the Russian Federation. Although the level of universities annual income was a significant factor in international competitiveness, university management efficiency played an important role, not only increased funding. Universities with greater institutional management freedom will have greater international competitiveness.